Antioxidant and hypolipidemic effects of soymilk fermented via Lactococcus acidophilus MF204. Issue 12 (31st October 2017) - Chen, Jie; Wu, Yan; Yang, Chunmei; Xu, Xuejiao; Meng, Yuecheng
Abstract : Previous studies have shown that fermentations can enhance the bioactivity and absorption rate of soybean products. Abstract : Previous studies have shown that fermentations can enhance the bioactivity and absorption rate of soybean products. Fermented soybean products can alleviate hyperlipidemia and decrease risks of atherosclerosis and cardiovascular diseases. This study aimed to investigate the effects and mechanisms of soymilk fermented by Lactococcus acidophilus on blood lipids and antioxidant enzyme activities of rats fed with a high fat diet. Sixty rats were randomly assigned to six groups: normal control group (NC), high-fat control group (HFC), positive control group (cholestyramine, PC), Lactococcus acidophilus group (LA), soymilk group (SM), and fermented soymilk group (FSM), respectively. The NC group was fed with a basic diet, while the other groups were fed with a high-fat diet. After the experimental period (6 W), rats were sacrificed by decapitation. Blood and liver were collected to measure the concentrations of lipids and antioxidant enzyme activities. Results demonstrated that fermented soymilk could regulate lipid levels, restore HDL-c and TG to normal levels, and lower the concentrations of LDL-c than hypolipidemic drugs in hyperlipidemia rats. More importantly, fermented soymilk caused significant reduction in arteriosclerosis index and coronary risk index. Fermented soymilk also improved antioxidant capacities of hyperlipidemia rats. The increase of aglycone isoflavones in fermented soymilk could explain the above phenomena. In conclusion, soymilk fermented by Lactococcus acidophilus reduced risks of arteriosclerosis and coronary heart disease by regulating lipid levels and improving the antioxidant capacities of hyperlipidemia rats.